Employee financial participation in businesses: Is it worth discussing? - Barbara Blaszczyk (Center for Social and Economic Research (CASE), 2014)
This paper is an overview of the achievements in the area of employee financial participation (EFP) during the last fifty years. It addresses the question of the extent to which EFP is relevant in today's world. EFP is distinguished from participation in management (industrial democracy), and the various types of EP are discussed. The major arguments for EFP are presented and discussed critically. The evolution of major forms of EFP, the scale of their operation in several advanced economies, and the legal and tax incentives for EFP are described. The efforts of European Union bodies to popularise this idea in all member countries are illustrated. Showing that EFP has become a broadly recognised principle of modern management in thousands of enterprises, we consider opportunities for disseminating these solutions on a wider scale, in particular in Poland. Finally, a number of directions for further research on financial participation are considered.
Keywords: A13; D02; G32; J54; M52; P12; 330; Financial participation; industrial democracy; employee saving plans; profit sharing; employee share ownership; employee share ownership plans; legal regulations; incentives; European countries; USA